Review of Psychosocial Aspects of Mothers with Eclamsia or Preeclamsia: Integrative Review - Sari, Aninditya Ajeng Avilia; Rahayuningsih, Faizah Betty; Widarini, Sinta Rahmania Ayu (GLOBAL HEALTH SCIENCE GROUP, 2024)
This study explores the psychosocial impact of preeclampsia on patients and their Background: This study explores the psychosocial impact of preeclampsia on patients and their families, and its effect on long-term well-being. Objective: It also aims to develop strategies to mitigate the negative effects and enhance overall well-being. Method: Using a comprehensive literature review, the study analyzed 22 journals published between 2020 and 2024, sourced from PubMed, Google Scholar, and Cochrane, with specific keywords related to preeclampsia and nursing care. Result: This study analyzed 22 journals out of 256 journals, journals were selected based on the keywords preeclampsia, eclampsia and nursing care, then re-filtered based on title and abstark into 59 article journals, then re-filtered based on the suitability of the full text of each journal into 22 journals and categorized psychosocial impacts into five main aspects: patient and family impact, emotional well-being, eclampsia management, traumatic experiences, and psychosocial support. Significant emotional and mental effects, such as anxiety and stress, lower quality of life. The study emphasizes the need for psychosocial interventions such as counseling and emotional support to address these issues and improve adaptation. The long-term impact of preeclampsia on emotional well-being highlights the importance of comprehensive care, including education and support to manage eclampsia and HELLP syndrome. Conclusion: Effective psychosocial support and healthcare worker knowledge are crucial in mitigating the psychological burden and improving patient outcomes.